2021
DOI: 10.15376/biores.16.2.3298-3303
|View full text |Cite
|
Sign up to set email alerts
|

Strength and stiffness of 8-Inch and 12-Inch deep mixed oak bolt-laminated timber mats

Abstract: Ground support provided by crane mats ensures the safety of workers and integrity of heavy-duty machines. Analytical evaluation of timber mats is necessary to advance the development of engineering standards associated with wood-based as well as other types of mats. The goal of this study was to mechanically evaluate bending stiffness and strength of timber 8-inch and 12-inch deep mixed oak bolt-laminated timber mats. The 8-inch-deep specimen dimensions were 24 inches wide and 12 feet long, while 12-inch-deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As part of graduate research, Herberg (2018) reported on the bending performance of nail-laminated crane mats. Others have reported on the mechanical properties of mixed hardwood bolt-laminated 8-inch deep mats (Owens et al 2020) and mixed oak bolt laminated 8-and 12-inch deep mats (Shmulsky et al 2021). While these research findings detail varying aspects of the flexural behavior of mats or mat components, none speaks to the behavior or design properties of three-ply, mechanically fastened, hardwood mats.…”
Section: Introductionmentioning
confidence: 96%
“…As part of graduate research, Herberg (2018) reported on the bending performance of nail-laminated crane mats. Others have reported on the mechanical properties of mixed hardwood bolt-laminated 8-inch deep mats (Owens et al 2020) and mixed oak bolt laminated 8-and 12-inch deep mats (Shmulsky et al 2021). While these research findings detail varying aspects of the flexural behavior of mats or mat components, none speaks to the behavior or design properties of three-ply, mechanically fastened, hardwood mats.…”
Section: Introductionmentioning
confidence: 96%